Níveis e tipos de fibra dietética para suínos pesados em restrição alimentar qualitativa - Rodrigues, Daniela Junqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Two trials were realized to evaluate diets with increasing levels of soluble and insoluble fiber in the feeding of finishing pigs for late slaughter, in a qualitative feed restriction program, on the growth performance, the digesta rate of passage, the diets digestibilities, the characteristics of the feces, the carcass traits, the meat quality, the fatty acids profile of the meat, the gastrointestinal tract organs weights. In each one of the trials, 32 male pigs, were assigned in a randomized block design, to control the initial body weight variation, being four treatments and eight replications in each treatment. The treatments were a control diet, used for both trials (1.5 and 15.5 % of soluble and insoluble dietetic fiber, respectively); three diets with purified pectin addition to achieve the levels of 4, 8 and 12% dietary soluble fiber and other three with purified cellulose addition to achieve the levels of 20, 25 and 30% dietary insoluble fiber. The higher levels of dietetic soluble fiber caused prejudice (P<0.05) in the animal's performance, increased the passage rate of the digesta and in 44.84 day to achieve 130kg (81.53%).As well, the use of higher levels of soluble fiber increased the digestibility of total dietetic fiber in 11.04%, and the nitrogen, potassium and sodium presents in the feces in 20.31, 26.24 and 26.47%, respectively. In the carcass traits, the diets with increase of soluble fiber caused a linear reduction (P<0.05) on the yield, the backfat thickness, the loin area, the fat area, the ham weight and the lean meat quantity, but the higher level of soluble fiber, increased in 7.62% the percentage of lean meat. The increase of soluble fiber in the diets showed linear increases (P<0.05) to the relative weight of the digestive organs weights, exception the liver.The use of higher levels of insoluble fiber reduced (P<0.05) the energy intake, but this not affected (P>0.05) the animal's performance. The ...

Foram conduzidos dois experimentos com o objetivo de avaliar dietas com níveis crescentes de fibras, solúvel e insolúvel, na alimentação de suínos abatidos pesados submetidos a um programa de restrição alimentar qualitativa, sobre o desempenho, taxa de passagem da digesta, digestibilidade das dietas, composição e excreção de nutrientes e minerais nas fezes, características de carcaça, qualidade e perfil de ácidos graxos da carne, pesos de órgãos do sistema digestório. Para cada um dos experimentos realizados foram utilizados, 32 suínos machos castrados, distribuídos em um delineamento em blocos ao acaso, em função do peso vivo inicial, sendo quatro tratamentos e oito repetições por tratamento. Os tratamentos consistiram em uma dieta controle utilizada para os dois experimentos (com teores de 1,5 e 15,5% de fibra dietética solúvel e insolúvel, respectivamente); três dietas com adição de pectina purificada para atingir os teores de 4, 8 e 12% de fibra dietética solúvel (Experimento 1) e outras três com adição de celulose purificada para apresentarem 20, 25 e 30% de fibra dietética insolúvel (Experimento 2). O uso de maiores níveis de fibra solúvel na dieta prejudicou (P<0,05) o desempenho dos animais, proporcionou aumento (P<0,05) na taxa de passagem da digesta e de 44,84 dias necessários para atingir 130kg de peso vivo (81,53%). Os maiores níveis aumentaram a digestibilidade da fibra dietética total em 11,04% e a porcentagem de nitrogênio, potássio e sódio excretados nas fezes, em 20,31; 26,24 e 26,47%, respectivamente. Na avaliação das características de carcaça, os níveis crescentes de fibra dietética solúvel proporcionaram redução linear (P<0,05) para o rendimento, espessura de toucinho média, área de olho e lombo e de gordura, peso de pernil e quantidade de carne magra, enquanto a porcentagem de carne magra na carcaça demonstrou aumento linear (P<0,05) de 7,62%, com o maior nível ...
Keywords: Suino; Fibras na nutrição animal; Celulose; Pectina; Restrição calórica; Cellulose